Peran Dinas Lingkungan Hidup pada Pengelolaan Sampah di Kota Pekanbaru - Novia Gardini; Zulkarnaini Zulkarnaini (Badan Penerbit STIEPARI Press, 2025)
Waste management is a critical issue in urban environmental management, especially in Pekanbaru, which faces challenges related to the increasing volume of waste due to population growth and urbanization. This study aims to analyze the role of the Environmental Agency (Dinas Lingkungan Hidup - DLH) of Pekanbaru in waste management and the effectiveness of policies implemented to reduce and manage waste in the city. This research uses a qualitative descriptive approach, with data collection techniques including in-depth interviews, field observations, and a review of waste management policy documents. The research informants include officials from the Environmental Agency, waste management staff, and members of the community involved in cleanliness programs. The findings indicate that the role of DLH is crucial in waste management, but several challenges remain, such as the lack of waste sorting facilities at the household level, low community participation, and budget limitations for sustainable waste management programs. Nevertheless, some policies, such as community education and the development of waste management infrastructure, have shown positive results, although further evaluation and improvement are needed. This study recommends better coordination among relevant agencies, increased community participation, and greater budget allocation to support more effective waste management in Pekanbaru.